Ratio of early warning system and risk based capital in insurance companies registered at OJK 2016-2020 - Muhamad Syahwildan; Parulian (Privietlab, 2022)
The purpose of this study is to analyze the effect of the early warning system ratio which is proxied in the ratio of the level of adequacy of funds, the ratio of claims expense and the ratio of liquidity to risk based capital in insurance companies registered with the OJK in 2016 - 2020. Risk based capital is a ratio that describes the solvency of the company. insurance. The population in this study is the annual financial statements of life insurance companies registered with the OJK Financial Services Authority in Indonesia from 2016 - 2020 with a population of 20 companies and the sample used is 20 life insurance companies registered with the Financial Services Authority (OJK). . The sampling technique in this study used a saturated sampling technique. This study uses the Eviews version 10 tool. The findings in this study show that the ratio of the level of adequacy of funds, the ratio of claims expense, and the liquidity ratio partially and simultaneously has an effect on risk based capital.